Answer:
c
Explanation:
y = 5x² - 17x - 12
to find the roots let y = 0 , that is
5x² - 17x - 12 = 0
Factorising the quadratic
consider the factors of the product of the coefficient of the x² term and the constant term which sum to give the coefficient of the x- term
product = 5 × - 12 = - 60 and sum = - 17
the factors are - 20 and + 3
use these factors to split the x- term
5x² - 20x + 3x - 12 = 0 ( factor first/second and third/fourth terms )
5x(x - 4) + 3(x - 4) = 0 ← factor out (x - 4) from each term
(x - 4)(5x + 3) = 0
equate each factor to zero and solve for x
x - 4 = 0 ⇒ x = 4
5x + 3 = 0 ⇒ 5x = - 3 ⇒ x = -
= - 0.6
roots are (4, 0 ) and (- 0.6, 0 )